Analisis Faktor yang Mempengaruhi Keputusan Penggunaan Qris pada Generasi Z - Selly Rachmawati; Tri Nur Wahyudi (Universitas Muhammadiyah Malang, 2024)
Purpose: The research aims to analyze the influence of lifestyle, financial literacy, benefits, ease, security and confidence on the decision to use QRIS as a modern payment method on Generation Z born on 1997–2012 and using QRIS payments. Methodology/approach: The research used quantitative data with random sampling from Generation Z respondents. Using descriptive analysis, double regression analysis and data analysis techniques : validity and reliability test, normality test, multicolonierity test, heteroskedasty test, simple linear regression analytics test, partial t-test, simultaneous f-test and determination coefficient test. Findings: The resulth of this study showed that lifestyle, benefits and security variables influenced (positively) the decision to use QRIS in Generation Z. While the financial literacy, ease and trust variables did not inluence (negatively) QRIS use decisions in Generation Z. Practical and Theoretical contribution/Originality: The research contributes to modern and practical transaction activities that can reduce conventional transactions so as to increase revenue and increase knowledge about the use of cashless payment applications. Research Limitation: The research is limited only to the Z Generation. The spread is not at its maximum so subsequent censorship will expand the population spread in data acquisition